Fabrication of a Cation Exchange Membrane with Largely Reduced Anion Permeability for Advanced Aqueous K‐ion Battery in an Alkaline‐Neutral Electrolyte Decoupling System. Issue 6 (1st December 2022) - Dong, Wenju; Li, Luping; Cheng, Shuang; Huang, Longjun; Yang, Lexuan; Liu, Yuxiu; Yao, Huan; Liu, Chenxu; Liu, Weizhen; Ji, Xu
Abstract: Herein, an efficient method to prepare sulfonated polyether ether ketone (SPEEK) based cation exchange membranes (CEMs) is developed, where polyethersulfone (PES) is used as an additive. The optimized membrane of 30 wt.%PES/SPEEK‐M exhibits a rather low anion permeability and a high ionic conductivity of 9.52 mS cm −1 together with low volume swelling in water. Meanwhile, tensile strength of the membrane is as high as 31.4 MPa with a tensile strain of 162%. As separators for aqueous K‐ion batteries (AKIBs) with decoupled gel electrolytes (Zn anode in alkaline and Prussian blue (FeHCF) cathode in neutral). Discharge voltage of the AKIB can reach 2.3 V. Meanwhile, Zn dendrites can be effectively suppressed in the gel anolyte. Specific capacities of the FeHCF cathode are 116.7 mAh g −1 at 0.3 A g −1 (close to its theoretical value), and 95.0 mAh g −1 at 1.0 A g −1, indicating good rate performance. Capacity retention of the cathode is as high as 91.2% after 1000 cycles' cycling owing to the well remained neutral environment of the catholyte. There is almost no pH change for the catholyte after cycling, indicating good anion‐blocking or cation‐selecting ability of the 30 wt.%PES/SPEEK‐M, much better than other membranes. Abstract : An efficient cation exchange membrane is prepared for an aqueous K‐ion battery with decoupling electrolyte (zinc foil anode in alkaline electrolyte and Prussian blue cathode in neutral electrolyte). The electrolyte decoupling strategy maximizes the operating window of the system to 2.6 V and the membrane can effectively block anion shuttling and smoothly conduct cations to ensure long‐term normal operation.